2005
DOI: 10.1152/ajpheart.00868.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherogenic potential of red wine: clinician update

Abstract: Complications of atherosclerosis remain the leading cause of morbidity and mortality in industrialized countries. Epidemiological studies have repeatedly demonstrated that moderate alcohol intake has a beneficial effect on cardiovascular disease. The purpose of this review is to examine the epidemiological and biological evidence supporting the intake of red wine as a means of reducing atherosclerosis. On the basis of epidemiological studies, moderate intake of alcoholic beverages, including red wine, reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 116 publications
1
28
0
3
Order By: Relevance
“…Uma das ferramentas que se dispõe para avaliar in vitro essa propriedade biológica protetora é a medida da atividade antioxidante dessas bebidas. Em geral, propriedades anticarcinogênicas, antiinflamatórias e antimicrobianas estão relacionadas à capacidade que os compostos fenólicos apresentam em eliminar radicais livres, o que, por sua vez, evita, em certo grau, a oxidação de lipoproteinas, como o LDL (low density lipoprotein), agindo, assim, na prevenção de doenças vasculares (PEARSON et al, 1999;MARTÍNEZ-FLÓREZ et al, 2002;SZMITKO;VERMA, 2005).…”
Section: Análise Estatísticaunclassified
“…Uma das ferramentas que se dispõe para avaliar in vitro essa propriedade biológica protetora é a medida da atividade antioxidante dessas bebidas. Em geral, propriedades anticarcinogênicas, antiinflamatórias e antimicrobianas estão relacionadas à capacidade que os compostos fenólicos apresentam em eliminar radicais livres, o que, por sua vez, evita, em certo grau, a oxidação de lipoproteinas, como o LDL (low density lipoprotein), agindo, assim, na prevenção de doenças vasculares (PEARSON et al, 1999;MARTÍNEZ-FLÓREZ et al, 2002;SZMITKO;VERMA, 2005).…”
Section: Análise Estatísticaunclassified
“…When the effect of consumption of this substance is analyzed in an acute manner, moderate doses provide BP decrease in SHR 27 . When red wine is consumed, regardless of the presence or absence of alcohol, poliphenols play a cardioprotective role, since they have an antioxidant action on LDL-cholesterol 11,14,15 and inhibit proinflammatory proteins 16 . Studies using alcohol-free red wine compounds showed that in hypercholesterolemic rabbits 28 and rats 29 , the phenolic compound had an antithrombotic role as a result of platelet aggregation inhibition.…”
Section: Soares Filho Et Al Effect Of Red Wine and Physical Exercise mentioning
confidence: 99%
“…Moderate consumption of some types of alcoholic beverages, including red wine (one to two daily doses), shows an inverse association with the development of coronary artery disease (CAD) 10,11 . In a meta-analysis 12 which involved 13 studies, the benefits of red wine have incorporated more support because it was shown 32% reduction in the development of atherosclerotic disease in wine consumers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratol has been repeatedly invoked to explain the so-called French Paradox, i.e., the lower incidence of cardiovascular diseases in the French population despite a diet very reach in saturated fats, 27 and to be related to all the subsequent epidemiological studies which correlated moderate consumption of red wine with reduced risk for a series of diseases. 27,28 In laboratory studies, this polyphenol has been shown to have many beneficial actions in mammals, such as anticancer, 29,30 anti-atherogenetic, 28,31,32 anti-inflammatory, 33 estrogenic, it inhibits platelet aggregation in vivo and in vitro, 34,35 is antioxidant and chemopreventive, 36 as it was also shown to inhibit cytochrome P450 enzymes in human cells, 37,38,39 which plays a very important action in the conversion of pro-carcinogens into carcinogens. One of resveratrol's much studied property is its protective action on ischemic damage in the brain, 40 kidney 41 and hearth.…”
Section: Resveratrolmentioning
confidence: 99%